Towards a Methodological Scheme-Interpretation - Lenk, Hans (Aufklärung: journal of philosophy, 2018)
Any kind of knowledge, cognition, perception, and action is necessarily shaped by (re)activation of "schemata". Any interpretation is schema (re)activation. Schemata are epistemologically speaking "structural" activation patterns which are psychologically and neurologically speaking accommodated, adapted, "learned" by (co- and re)activating neuronal assemblies. Six levels of interpretative schema activations (schema interpretations) are outlined from invariable primary "interpretations" through conventional, classificatory and justificatory as well as meta-interpretations. Constitutive schema interpretations are unavoidable. Many philosophical problems will have to be reformulated or reinterpreted along these lines.